Food environments in the Pacific Region and efforts to improve them: A scoping review - Sela Ki Folau Fusi; Clara Gómez-Donoso; Kathryn Backholer; Jennifer Browne; Megan Ferguson; Adrian J Cameron
Abstract Objective: To understand the characteristics of food environments in the Pacific region, and the broader economic, policy, and sociocultural surroundings that influence food choices and interventions to improve food environments for Pacific communities. Design: Systematic searches were conducted for articles related to food environments or factors influencing food choices from 1993-2024 in five academic databases, Google, Google Scholar, and relevant organizations' websites. Studies were included if they meet the eligibility criteria. Two authors independently reviewed the title and abstract of identified articles. Full-text screening was conducted before data was extracted from eligible studies. A narrative analysis was informed by an existing food environments framework. Setting: Pacific Island countries or territories that are a member of the Pacific Community (SPC). Participants: Not Applicable. Results: From the 66 included studies (of 2520 records screened), it was clear that food environments in the Pacific region are characterized by high availability and promotion of ultra-processed unhealthy foods. These foods were reported to be cheaper than healthier alternatives and have poor nutritional labelling. Food trade and investment, together with sociocultural and political factors, were found to contribute to unhealthy food choices. Policy interventions have been implemented to address food environments; however, the development and implementation of food environment policies could be strengthened through stronger leadership, effective multisectoral collaboration and clear lines of responsibility. Conclusions: Interventions focused on improving physical, economic, policy, and sociocultural influences on food choices should be prioritized in the Pacific region to improve the food environment and mitigate barriers to healthy eating.